Advances in Diagnostic Techniques for Influenza Virus Infection: A Comprehensive Review - Qi Qian; Guohao Fan; Wei Yang; Chenguang Shen; Yang Yang; Yingxia Liu; Weiwei Xiao (Tropical Medicine and Infectious Disease, 2025)
Influenza poses a significant global health burden due to its high transmissibility, antigenic variability, and substantial morbidity. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has further complicated influenza dynamics, highlighting the need for rapid, accurate, and accessible diagnostics. This review comprehensively summarized the advancements in influenza virus (IFV) detection, from conventional methods like viral culture and serology to modern molecular techniques, including CRISPR-based systems, next-generation sequencing (NGS), and biosensors. We analyze the sensitivity, specificity, and applicability of these methods and emphasize their roles in clinical and public health settings. While traditional techniques remain valuable for strain characterization, novel technologies like CRISPR and portable biosensors offer rapid, low-resource solutions. This review provides a comprehensive insight into the development of integrated diagnostic strategies for seasonal IFV epidemics and future pandemics.